Farmers Markets and Single-Use Plastic: Why Environmentally Conscious Consumers Don’t Bring Reusable Bags - Scott Hardy; Jill Bartolotta ([TEST] Journal of Extension, 2021)
This study looks at the role of Extension in helping local officials reduce plastic bag use at farmers markets in three Lake County, OH communities. We distributed free reusable bags to shoppers and conducted an education and outreach program. We then took observations to determine if the free reusable bags were being used. We also invited shoppers to take a voluntary survey about their environmental attitudes, why or why not they use the reusable bags, and how best to reduce plastic bag use moving forward. Results from the study suggest that supplying free reusable bags at farmer markets is not an effective strategy for Extension professionals attempting to reduce plastic bag use. Instead, we recommend working with local officials to develop financial incentives and disincentives tied to the type of bag option shoppers use, implement plastic bag bans at markets, and conduct locally-focused education and outreach. Although shoppers’ environmental literacy and desire for sustainability is high, it is shown that behavior change is unlikely to occur without financial or policy incentives.
Keywords: Extension; plastic bags; behavior change; farmers markets; sustainability